The adolescent with obesity: what perspectives for treatment? - Antonio Nicolucci; Claudio Maffeis (BMC, 2022)
Abstract The dramatic increase in overweight and obesity among children and adolescents has become a major public health problem. Obesity in children and young adults is associated with an increased prevalence of cardiometabolic risk factors. Obesity during adolescence represents a strong predictor of obesity and higher mortality in adulthood. Due to the serious implications of obesity in adolescents, effective treatments are urgently needed. Lifestyle interventions represent the recommended therapy. Nevertheless, real world data show that the majority of adolescents do not achieve weight loss in the long term, and are reluctant to participate in lifestyle interventions. Pharmacological treatment is recommended if a formal lifestyle modification program fails to limit weight gain or to improve comorbidities. However, until 2020 the European Medicines Agency (EMA) had not approved any pharmacotherapeutic agents for obesity in pediatric patients. On April 2021, EMA has authorized the use of Liraglutide, a glucagon-like peptide (GLP)-1 analog, for the treatment of obesity in adolescents (12-17 years). The efficacy and safety of Liraglutide were demonstrated in a randomized, double-blind trial, enrolling 251 adolescents. After 56 weeks, a reduction in BMI of at least 5% was observed in 43.3% of participants in the liraglutide group vs. 18.7% in the placebo group, and a reduction in BMI of at least 10% was observed in 26.1 and 8.1%, respectively. Gastrointestinal events were the events most frequently reported with liraglutide. Bariatric surgery represents another effective treatment for adolescents with severe obesity, with sustained benefits on weight loss and cardiometabolic risk factors. However, long-term safety and effectiveness data in adolescents are still scarce. Risks of bariatric surgery include the need for additional abdominal surgical procedures and specific micronutrient deficiencies. Hopefully, new pharmacological treatments in addition to lifestyle interventions will offer more chances of success.